Malthus to modernity: England's first fertility transition, 1760-1800 - Gregory Clark; Neil Cummins (University of California, Department of Economics, 2010)
English fertility history is generally regarded as having been composed of two re-gimes: an era of unregulated marital fertility, from at least 1540 to 1890, then the modern era, with regulated marital fertility, lower for higher social classes. We show there were in fact three fertility regimes in England: a Malthusian regime which lasted from at least 1500 until 1780, where fertility was substantially higher for the rich, an intermediate regime from 1780 to 1890 with fertility undifferentiated by class, and finally the modern regime. Wealthy English men produced substantially fewer children within a generation of the onset of the Industrial Revolution, over 100 years before the classic demographic transition. At the same time the fertility of the poor increased. Determining what triggered this change, however, and why it coincided with the Industrial Revolution, will require further research.
Keywords: 330